Core summary for IODP Site 389-M0102 - Webster, Jody M; Ravelo, Ana Christina; Grant, Hannah; Stewart, Margaret S; Rydzy, Marisa; Le Ber, Erwan; Allison, Nicola; Asami, Ryuji; Boston, Brian; Braga, Juan-Carlos; Brenner, Logan; Chen, Xuefei; et al. (PANGAEA, 2025)
List of cores recovered from the above given site on International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs) during the offshore phase of this expedition. The offshore phase took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai'i, USA. Cores have been acquired by Benthic's fifth-generation Portable Remotely Operated Drill (PROD5). According to IODP core type nomenclature, cores recovered by push coring mode are labelled by the letter P, those recovered by rotary coring mode are labelled by the letter "R" and the letter "W" indicates intervals drilled without coring in wash down mode. For further methodological information see methods chapter in Webster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025
Keywords: central Pacific; Coral Reef; Earth climate feedbacks; Earth history tipping points; Expedition 389; Hawaiian Drowned Reefs; Hawaiian geology; International Ocean Discovery Program (IODP); MMA Valour; Paleoclimate; sea level; volcanic